Application of Black Liquor Derived Carbonaceous Compound as Fuel in Direct Carbon Fuel Cell - Teoh, Shu Wei; Yoon, Li Wan; Wong, Wai Yin; Low, Jiun Hor (International Journal of Integrated Engineering, 2022)
Direct carbon fuel cell (DCFC) with higher power efficiency and lesser emissions is being viewed as a potential clean energy source. The application of renewable biochar as fuel for DCFC is found to be feasible to replace coal or carbon black for power generation. Black liquor from the paper production might be a suitable fuel source for DCFC due to its high lignin or carbon content. In this study, the feasibility of using compound extracted from black liquor as fuel source for DCFC was investigated in the aspect of physico-chemical and electrochemical properties. Suitable pyrolysis temperature in producing biochar from black liquor compound was first investigated. Results have shown that fixed carbon and ash content increased slightly with increasing pyrolysis temperature. The ash content is made up of majority of silica as depicted in FESEM-EDX results. Oxygen containing functional group was decomposed under high pyrolysis temperature of 700°C and 800°C. Besides, biochar obtained at 500°C of pyrolysis temperature has given the highest power density of 1.22 mW cm-2 whereas 1.44 mW cm-2 was obtained from coal which was used as the control. Future work on ash removal from the black liquor prior to pyrolysis might improve the potential of black liquor derived compound as a fuel source for DCFC.